PENGARUH PENYULUHAN TENTANG PERKEMBANGAN MOTORIK KASAR ANAK USIA 0 â 1 TAHUN TERHADAP PENGETAHUAN IBU - Sumirat, Widhi (Akademi Keperawatan Pamenang, 2013)
Motherâs knowledge about growth of harsh motorik of age child 0 â 1 year represent basic knowledge which must have by mother. This matter because of with good motherâs knowledge will assist process grow child flower, specially harsh motorik. Knowledge of mother got to through various education program among otherâs is counseling health, in this time still met by delay of growth of harsk motorik at age child 0 â 1 year and knowledge of mother there is nothink. Target or the research is to know knowledge of mother before and after doing of counseling and also know influence performing of counselling.Research desain the use is pre eksperimental with approach one group pre post desain. Population having age child 0 â 1 year in Posyandu Anggrek Orchad Watugedhe Countryside Watugedhe District Puncu Kediri, with system random sampling a number of 14 mother. Data analysis conducted by comparing knowledge before and after counseling, analiyticly statistical with statistical test of Wilcoxon.From result of statistical test of Wilcoxon got by result (Ï=0,001) <Â (Î±=0,05) with value of Confiden International that is mistake storey : level equal to (Î±) 5% and trust 95%, with the meaning Ho refused and H1 accepted to indicate that there is influence of counseling about growth of harsh motorik of age 0 â 1 year.Â Keyword : Knowledge, Counselling.